REVITALISASI KAMPUNG INGGRIS BERBASIS WISATA DI NEGERI SAWAI KECAMATAN SERAM UTARA MALUKU TENGAH - Ilona F. Salhuteru; Nurlaila Tuanany; Franklin Untailawan; Febby W. Pelupessy; Thobias Sarbunan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2022)
Community Service activities carried out by IAKN Ambon lecturers in Negeri Sawai, North Seram District, Central Maluku Regency are focused on revitalizing the program. This program is implemented by the Provincial Government in 2019. The activity of PkM was held in 4 days (14-17 September 2021). The activities carried out in this PkM include: designing a grand design of a tourism-based English village program and improving English language skills for young people in Sawai. In addition, the PkM activity also aims to train young people to create learning media which is environmentally friendly, fun learning strategies and improving public speaking skills related to tourism. The implementation of PkM activities went smoothly because the people in Sawai supported the activities. They expect this activity could continue in the future. This is essential because they need assistance in running the tourism-based English village program in Sawai.